Extracellular electron transfer mechanisms between microorganisms and minerals - Shi, Liang; Dong, Hailiang; Reguera, Gemma; Beyenal, Haluk; Lu, Anhuai; Juan Liu; Yu, Han-Qing; Fredrickson, James K (Nature Reviews Microbiology, 2016)
Electrons can be transferred from microorganisms to multivalent metal ions that are associated with minerals and vice versa. As the microbial cell envelope is neither physically permeable to minerals nor electrically conductive, microorganisms have evolved strategies to exchange electrons with extracellular minerals. In this Review, we discuss the molecular mechanisms that underlie the ability of microorganisms to exchange electrons, such as c-type cytochromes and microbial nanowires, with extracellular minerals and with microorganisms of the same or different species. Microorganisms that have extracellular electron transfer capability can be used for biotechnological applications, including bioremediation, biomining and the production of biofuels and nanomaterials.